2004
DOI: 10.1042/bj20031733
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide metabolite, not intact ceramide molecule, may be responsible for cellular toxicity

Abstract: Ceramides, which are produced from the hydrolysis of sphingomyelin or synthesized from serine and palmitate in a de novo pathway, are regarded as important cellular signals for inducing apoptosis. However, controversy over this proposed role of ceramides exists. Using stable isotope labelling coupled with GC (gas chromatography)-MS and mass isotopomer distribution analysis, we have studied the metabolism of exogenous long-chain ceramides in HL60 cells. Our results do not support the concept of enhanced ceramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…agreement with a recent report (22), the presence of dodecane did not enhance the uptake and metabolism of fluorescent NBD-Cer, which was followed in parallel (Fig. 5).…”
Section: Discussionsupporting
confidence: 80%
“…agreement with a recent report (22), the presence of dodecane did not enhance the uptake and metabolism of fluorescent NBD-Cer, which was followed in parallel (Fig. 5).…”
Section: Discussionsupporting
confidence: 80%
“…Few studies have reported the status of dihydroceramide during apoptosis. Interestingly, Tserng and Griffin (40) recently reported the same pattern of dihydroceramide, but not ceramide, accumulation along with cell death when HL-60 human leukemia cells were treated with natural ceramide or N-oleoylethanolamide, a ceramidase inhibitor, as well as its inactive homologue, Npalmitoylethanolamide (40). Our current data, together with those gathered by Tserng and Griffin, therefore, indicate that this pattern of dihydroceramide and dihydrosphingosine accumulation is independent of the cell types and the reagents applied and therefore may represent a previously unrecognized type of cellular response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Jiang et al (39) could also demonstrate for the chemotherapeutic g-tocopherole, which blocks the DEGS, that an accumulation of endogenously produced C 16:0 -dhCer induces apoptosis in lung cancer cells (A549). Moreover, Tserng and Griffin (40) elucidated that natural C 16:0 -Cer exogenously added to human leukemia cells induces apoptosis via accumulation of dhCers. Deregulation of dhCer and Cer levels in fibroblasts, caused by the loss of the CLN9 gene, has dramatic consequences for cell growth, inasmuch as these cells show rapid growth on the one hand but increased apoptosis on the other hand (41).…”
Section: Discussionmentioning
confidence: 99%